Development of Interactive E-Module Using Kvisoft Flipbook Maker on Qurban and Aqiqah Materials Class X at MAN 2 Jombang - Hasanah, Siti Nikmatun; Sholihah, Fatikhatun Nikmatus; Meishanti, Ospa Pea Yuanita (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
This research is based on the teaching materials available only in the form of printed books, student worksheets, and learning modules. However, the available teaching materials have not utilized today's technology. Qurban and Aqiqah materials teachers have never developed an electronic module. For this reason, teaching materials such as e-modules are needed that can be used by all students in accordance with their development so that students can easily understand the learning material. The purpose of this study is to determine the validity of e-modules using kvisoft flipbook maker on Qurban and Aqiqah materials. This type of research is research and development, the development model used is a 4D development model consisting of define, design, develop, and disseminate, but in this research it is only carried out up to the develop stage. To assess the product designed by the researcher, in this study, a validity test was carried out by media experts and material experts on the e-module using kvisoft flipbook maker. Based on the research that has been conducted, it can be known that the results of the validity of the e-module using kvisoft flipbook maker on Qurban and Aqiqah materials from media experts obtained a percentage of 92.5% with the Very Valid category. Meanwhile, the validity results from material experts obtained a percentage of 95.3% with the Very Valid category. This shows that the e-module using kvisoft flipbook maker on Qurban and Aqiqah materials is suitable for use in the learning process.